Test the Effect of Miana Leaf Ethanol Extract on Ureum and Creatinine Levels in Male White Rats - Joni Tandi; Yustin Yustin; Rezky Yanuarty; Tien Wahyu Handayani (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
This study aims to determine the content of secondary metabolites in miana leaf ethanol extract, and to determine the effective dose of miana leaf ethanol extract in reducing urea and creatinine levels in male white rats. This study used 30 rats divided into 6 treatment groups, each group consisting of 5 test animals, namely normal group, negative control, positive control, dose of 150 mg/kg BW, dose 200 mg/kg BW, and dose 250 mg/kg. kg body weight. The data obtained will then be tested for normality and homogeneity to find out the data is normally distributed and homogeneous. If the data is normally distributed and homogeneous, then it is continued using One Way Anova statistical analysis at a 95% confidence level and further LSD test is carried out. If the data obtained is not normal and homogeneous, then it is analyzed using non-parametric statistics Kruskal-Wallis test and continued with Mann Whitney further test to determine the difference between all treatments. The results showed that the ethanolic extract of miana leaves contained secondary metabolites of alkaloids, flavonoids, saponins,and tannins; miana leaf ethanol extract has an effect on reducing urea and creatinine; Miana leaf ethanol extract at a dose of 250 mg/kg BW was an effective dose in reducing urea and creatinine with an average decrease of 18.8 mg/dl and 0.64 mg/dl.